Hormonal status in patients with advanced prostatic cancer on the therapy with androgen blockade - Vojinov Saša; Levakov Ivan; Jeremić Dimitrije; Živojinov Srđan; Marušić Goran (Vojnosanitetski Pregled, 2011)
Background/Aim. Hormone suppression therapy is used in men with advanced prostate cancer improving chances of longer survival. The aim of this study was to investigate the influence of androgen blockades on testosterone and luteinizing hormone (LH) values in patients with locally advanced and metastatic prostatic cancer. Methods. The study included a total of 60 patients out of which 45 with prostatic cancer divided into 3 subgroups based on the type of the applied treatment protocol: 15 patients on monotherapy with luteinizing-releasing hormone (LH-RH) agonists (group I), 15 patients on total androgen blockade (group II) and 15 patients on monotherapy with antiandrogen (group III)). The control group consisted of 15 patients with benign prostatic hyperplasia. In all the patients, values of testosteron, LH and prostatespecific antigen (PSA) were monitored initially, as well as 3 and 6 months after the treatment protocol introduction. Results. In the patients of the groups I, II and III, values of testosterone decreased after three months by 95.58%, 95.72%, and 67%, respectively. The difference was significant (p < 0.01). Between the values after three and six months there was no significant difference in these groups of participants. Testosterone values were significantly higher in the patients of the group III in both analyses. Comparing the values between the groups III and I, as well as those of the groups III and II, a significant difference was found after three and six months of the therapy (p < 0.01). There was a difference in testosterone values between the groups I and II after 3 and 6 months, but not significant. All types of the applied treatment protocols in the therapy of prostatic cancer significantly decreased the values of LH compared to the basal ones. Conclusion. Total androgen blockade and LH-RH agonists are more effective in lowering testosterone values (to castration values) compared to the antiandrogen monotherapy, where testosterone values stay above the castration level. This therapy approach has advantages, since it decreases testosterone values providing better therapy response. There is a difference in testosterone values, but not significant, when total androgen blockade and monotherapy with LH-RH agonists are administered. Registered lower basal values of LH in all patients with prostatic cancer open the possibility to introduce LH as a new additional, significant marker in diagnosis of this neoplasm.